Obesity and risk of age-related eye diseases: a systematic review of prospective population-based studies - Ng Yin Ling, Clarissa; Lim, Su Chi; Jonas, Jost B; Sabanayagam, Charumathi (International Journal of Obesity, 2021)
Obesity is a public health challenge worldwide. The relationship between obesity and age-related eye diseases including cataract, glaucoma, age-related macular degeneration (AMD) and diabetic retinopathy (DR) have remained elusive. We conducted a systematic review of three electronic databases for longitudinal population-based studies that described associations between measures of obesity including body mass index (BMI), waist-circumference (WC), and waist-to-hip ratio (WHR), and age-related eye diseases. Our search yielded 1731 articles, of which 14, 10, 16 and 8 articles met our eligibility criteria for cataract, glaucoma, AMD and DR, respectively. BMI-defined obesity was positively associated with incident cataract, incident AMD and incident DR in Western populations, but in Asian populations associations for incident AMD were not significant and associations for incident DR were inverse. WC-defined obesity was associated with incident glaucoma in non-Western populations. WHR-defined obesity but not BMI-defined obesity was associated with the incidence or progression of AMD in two Western studies. Overall, we found strong evidence supporting associations between obesity and age-related eye diseases. Further research on the association of abdominal obesity and effect of weight loss and physical activity on age-related eye diseases is warranted to support clinical and public health recommendations.